Effects of multilingualism on brain structure, cognition and language processing - Yee, Jia’en (2022)
Recent evidence suggests that the control demands in multilingualism may diverge from that of bilingualism, and changes in brain structure and function occur with knowing more languages. Much remains to be understood regarding the ways in which multilingualism interacts with brain structure, cognition, and language processing. Firstly, while it is now understood through bilingualism research that certain brain regions adapt with increasing language experience, the trajectory and limits of these restructuring remain unclear as the number of languages one knows increases further, particularly so in subcortical structures. This is despite multilingualism being a common phenomenon in many parts of the world. Findings from past bilingual studies have shown patterns of volumetric expansions that are followed with reductions as language experience increases; possibly signifying renormalisation. Building upon the Dynamic Restructuring Model, the first study examined subcortical adaptations across 56 monolinguals, bilinguals, trilinguals and quadrilinguals using structural MRI. Volumetric analyses of five subcortical structures that underlie language control and processing were performed. The results uniquely show that structural adaptations of the caudate nucleus, nucleus accumbens, putamen, globus pallidus and thalamus are non-linear, and different structures renormalise with different amounts of experience. In the second study, multilingualism is examined deeper to include both the influence of both number of languages and literacy experiences on implicit statistical learning (ISL) as it is unclear if merely being able to speak more than one language would bring about cognitive advantages. Past studies have not investigated ISL despite it being fundamental in executive functions, and did not consider the effects of orthographic transparency despite the different demands in cognitive resources. Furthermore, opaque orthographies involve more statistical information and requires the employment of more implicit learning mechanisms. The results show that being multilingual does not confer benefits in ISL, but literacy in more opaque orthographies could improve ISL performance. This suggests that managing more opaque orthographies may help to develop greater capacities to detect statistical regularities of inputs and lead to greater competence and flexibility in extracting regularities in general. Finally, apart from interactions with brain structure and cognition, multilingualism relates with language processing in dynamic ways due to the multivalent combinations between different phonological and orthographic systems. For example, opaque orthographies require one to rely more heavily on phonological awareness (PA) and grow increasingly sensitive to both consistent and inconsistent correspondences between graphemes and phonemes. While bilingualism research has shown evidence of PA transfer across languages of different opacity, it is unclear if additionally taxing on phonological awareness through more opaque literacy experiences in multilinguals would bring about enhancements in this language processing function. Thus, in the last study, three groups of subjects who differed in their exposure to opaque orthographies were assessed on English rhyme judgements. The results of the behavioural phonological decision task show that more exposure to a bigger proportion of opaque orthographies is associated with better phonological processing. Overall, these three studies provide novel evidence, and advance our understanding of some ways in which multilingualism interacts with brain structure, cognition, and language processing.